IMPLEMENTASI UU NO. 16 TAHUN 2017 TENTANG ORGANISASI KEMASYARAKATAN DI KABUPATEN SUMEDANG - Ade Opik Rohmanudin (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2021)
The aim of this study is to find out the implementation of Law number 16 of 2017 on community organizations conducted of Sumedang Regency. This study used qualitative research methods. Data collection techniques are carried out through library research and field studies which include: observation, interviews, documentation study, and triangulation. Determination of sample/ informants in this study was carried out using purposive sampling and further analysis of data model by Miles and Huberman, namely: data reduction, data display, and conclusion drawing/verification. The results of this study are the finding of factors that support the implementation of the law number 16 of 2017 on community organizations to increase awareness of social organization of their obligations. In implementing the law it can be concluded thatKesatuan Bangsa dan Politik office of Sumedang Regency has done it well, but there are several obstacles, namely the lack of supporting resources in carrying out socialization, lack of understanding in the use of technology, and lack of understanding of community organizations regarding statutory policies regarding mass organizations and there is no written sanction for community organizations that do not give reports. The efforts to overcome these obstacles are increasing support resources, conducting socialization during surveys, and applying social sanctions.